2014
DOI: 10.1080/02602938.2014.986644
|View full text |Cite
|
Sign up to set email alerts
|

A written, reflective and dialogic strategy for assessment feedback that can enhance student/teacher relationships

Abstract: In response to the shortcomings of current assessment feedback practice, this paper presents the results of a study designed to examine students' and teachers' experience of engaging in a written, reflective and dialogic feedback (WRDF) strategy. The strategy was designed to enhance the learning experience of students undertaking a large first-year core course at a regional Australian university in semester 2, 2012. The evaluation consisted of three components: student surveys pre-and post-WRDF; a student focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…One informant knowingly said that their teacher prepared and gave them composition materials for she was with them for a long time. This finding concurs that by [26] who realized that continuous feedback can create and enhances the student-teacher relationship.…”
Section: Research Question Twosupporting
confidence: 91%
“…One informant knowingly said that their teacher prepared and gave them composition materials for she was with them for a long time. This finding concurs that by [26] who realized that continuous feedback can create and enhances the student-teacher relationship.…”
Section: Research Question Twosupporting
confidence: 91%
“…Ajawi & Boud, 2015;Crimmins et al, 2016) but students' preferences differ (Hepplestone & Chikwa, 2014) with some students favouring written comments only (Yang & Carless, 2013) and others appreciating a combination of written comments alongside one-to-one meetings with their lecturers (Blair & Mcginty 2012). One of the barriers to effective feedback in one-to-one's is explained by Poulus & Mahony (2008) who suggested that some students do not feel that they can interact with their lecturer due to their own confidence level and a lack of established relationship with their lecturer.…”
Section: Preferred Types Of Feedbackmentioning
confidence: 99%
“…The biggest issue in providing useful feedback seems to be that quality is compromised if academics are burdened with short turnaround times and/or too many students (Crimmins et al, 2016;McDonnell & Curtis, 2014;McNaught & Benson, 2015;Palmer, Levett-Jones, Smith & McMillan, 2014). Nicol (2009) suggests that this principle requires creating opportunities for students to receive early feedback (on drafts or formative tasks) and then making sure that students engage with the feedback and determine how they can use it in future assignments.…”
Section: Principle 3: Deliver High-quality Feedback Information That mentioning
confidence: 99%
“…One way of ensuring that students act on feedback is to oblige them to interact with the feedback before they undertake the next task. Crimmins et al (2016), for example, included a reflection on feedback activity where students were asked to determine what the feedback indicated and identify areas for improvement. This was then used to formulate questions for their tutor in a face-to-face session.…”
Section: Principle 4: Provide Opportunities To Act On Feedbackmentioning
confidence: 99%
See 1 more Smart Citation